Associated Factors the School Failure in the Secondary Education of Huelva - Carmen Márquez Vázquez (Universidad Autónoma de Madrid, 2016)
In this work we analyze the educational processes of the Secondary Education in Huelva. Mainly we focused in understanding those that end in school failure. To understand the school failure, we have observed the association between the educational performance and the individual, family factors and school organization that were previously identified by different theoretical approximations. The empirical work was carried out in eleven Institutes of Secondary Education. By using a mixed methodology, we could carry out a micro analysis of the factors referred to the student body and a meso-analysis of the factors referred to the centers. The results demonstrated the important dimension of the school failure in this context of education. Two key factors were identified associated of these educational problems. First of all, the level of familiar implication in the educational process and, secondly, the school organization. We have noticed that the school failure prevention requires proceeding in two different ways. On one hand, the review of the criteria of school grouping and tutorial designation that carry out the educational centers. On the other hand, an individualized intervention with the student body in risk that begins with the first symptoms of indifference and that is based on the constant cooperation between families and educational teams, so that they transmit to the students learning strategies that reinforce the individual motivation.